Arabian Sea monsoon experiment: An overview - RAO, P. SANJEEVA (MAUSAM, 2005)
The Arabian Sea Monsoon Experiment (ARMEX) is one of the land-ocean-atmosphere field experiments implemented in June-July 2002 and March-June 2003 under the Indian Climate Research Programme. The broad scientific objectives of the ARMEX are (i) to study the offshore trough embedded mesoscale vortices (Arabian Sea convection) associated with intense rainfall events on the west coast of India during monsoon period, and (ii) to study the evolution, maintenance and the collapse of the Arabian Sea warm pool and onset phase of the monsoon. Conventional weather monitoring systems, weather satellite observational systems, ships, met-ocean buoys, automatic weather stations, surface layer meteorological towers and aircraft were deployed with state-of-the-art instrumentation for this experiment. This paper attempts to provide an overview of the ARMEX scientific objectives, implementation strategy, resource mobilization, infrastructure deployed, observational data collation, archival and initial analysis by the participating scientists.